Artificial anterior cruciate ligament reconstruction - Alinejad, M (2014)
Conventional anterior cruciate ligament (ACL) reconstruction grafts have not been able to replicate the mechanical behaviour of the native ACL, reproduce normal knee mechanics and kinematics, or prevent degenerative disease progression of the knee. The aim of this thesis was to investigate a novel ACL design to more closely mimic the normal mechanical behaviour of the ACL, reconstruct the isometric ACL fibre and potentially reproduce the normal kinematics and mechanics of the knee. The designed artificial ACL reconstruction (ACLR) system could be used as a stand-alone device or in conjunction with a total knee replacement (TKR). The nominated design option for the ACLR system consisted of a connecting cord made of ultra-high molecular weight polyethylene (UHMWPE) fibres and an elastic system made of cobalt-chrome-molybdenum (CoCrMo) alloy with similar load-elongation characteristics to the native ACL. The design requirements were defined based on the mechanical properties of the native ACL, size constraints from the bony geometry and TKR components, and the location of the isometric fibres of the native ACL. The in vitro mechanical tests performed in this project on the designed cord showed a 2-3 times greater ultimate tensile load compared to the ACL in young human cadavers. The decreasing creep modulus of the UHMWPE cord under fatigue loading in simulated body conditions (3118 MPa at 6.5×106 cycle) indicated nominal creep and stabilised mechanical properties by the 3000th loading cycle. To replicate the non-linear stiffness of the ACL with ~38 N mm-1 toe and ~100 N mm-1 linear regions, the artificial ACLR device consisted of a femoral spring (~60 N mm-1) in series with a tibial spring (~100 N mm-1) and a connecting cord (~2000 N mm-1). Two helical springs in series were used for the stand-alone ACLR, whereas a helical spring in series with a spiral spring was designed for the ACLR-TKR. As both the helical and spiral springs had a constant stiffness, stop mechanisms were added to the springs to create a non-linear stiffness and control the maximum safe deformation limit of each spring. To understand the mechanical behaviour of the reconstructed isometric fibre of the ACL, passive and loaded motions were simulated in 18 sets of segmented MRI models of healthy human knees. Constant load and elongation was observed throughout flexion during the passive movements, whereas maximal load and elongation in the reconstructed ACL was identified at 50 º of flexion during loaded motion. An ACL attachment placement sensitivity study, conducted in this project to assess the effect of surgical implantation error on the behaviour of the reconstructed ACL, revealed that misplacement of the femoral attachment would significantly influence the load-elongation of the reconstructed ACL. Finite element (FE) models of the designed ACLR devices enabled their behaviour under simulated axial loading, squatting and the Lachman test to be assessed. Both ACLR devices successfully reproduced stiffness of the native ACL with a multi-linear stiffness curve, however, elongation greater than 3.1 mm could not be achieved. It can be concluded that the designed artificial ACLR devices were able to mimic the mechanical behaviour of the ACL provided it was positioned at the isometric attachment points; potentially enabling achievement of more natural kinematics and mechanics of the reconstructed knee. However, ACL placement was shown to have a significant impact on the behaviour of the reconstructed ACL, therefore, placement error may over-constrain the joint. For this reason, a more forgiving design with a lower stiffness and a larger deformation limit would be advised.